Psychometric Properties of the Person-Centered Version of the Alcohol and Alcohol Problems Perceptions Questionnaire (PC-AAPPQ). (15th July 2020) - Mahmoud, Khadejah F; Terhorst, Lauren; Lindsay, Dawn; Brager, Jenna; Rodney, Tamar; Sanchez, Michael; Hansen, Bryan R; Savage, Christine L; Seale, J Paul; Mitchell, Ann M; Johnson, J Aaron; Finnell, Deborah S
Abstract: Aims: Given the importance of addressing provider attitudes toward individuals with unhealthy alcohol use and the current emphasis on person-centered language to help decrease stigma and mitigate negative attitudes, the aim of this study was to evaluate the psychometric properties of a contemporary version of the Alcohol and Alcohol Problems Perception Questionnaire (AAPPQ) that uses person-centered language and addresses the spectrum of alcohol use. Methods: The authors created a person-centered version of the AAPPQ (PC-AAPPQ) and conducted a cross-sectional study of its psychometric properties in academic settings in the Northeastern United States. The PC-AAPPQ was administered to 651 nursing students. Reliability analysis of the new instrument was performed using the total sample. Only surveys with complete data ( n  = 637) were randomly split into two datasets, one used for the exploratory factor analysis (EFA) ( n  = 310) and the other for confirmatory factor analysis (CFA) ( n  = 327). Results: Compared to all the models generated from the EFA, neither the original six-factor structure nor the five-factor structure was superior to any of the other models. The results indicate that a seven-factor structure with all 30 items is the best fit for the PC-AAPPQ. Conclusions: The PC-AAPPQ represents a positive effort to modernize the four-decade-old AAPPQ. This 30-item instrument, which adds one additional subscale, offers a means to assess providers' attitudes using respectful wording that avoids perpetuating negative biases and reinforces efforts to affirm the worth and dignity of the population being treated.